(untitled) (International Journal of Culture and Art Studies, 2020)
The history of Twentieth Century Nigerian art is characterized by ambiguities that impede understanding of the underlying modernist philosophies that inspired modern art from the 1900s. In the past five decades, scholars have framed the discourse of Contemporary Nigerian Art to analyze art created during that period in Africa starting with Nigeria in order to differentiate it from that of Europe and America. However, this quest for differentiation has led to a mono-narrative which only partially analyze modernist tendencies in modern Nigerian art, thus, reducing its impact locally and globally. Adopting Content Analysis and Modernism as methodologies, this research subjected literature on Twentieth Century Nigerian art to critical analysis to reveal its grey areas, as well as draw upon recent theories by Chika Okeke-Agulu, Sylvester Ogbechie, Olu Oguibe and Okwui Enwezor to articulate the occurrence of a unique Nigerian avant-gardism blurred by the widely acclaimed discourse of contemporary Nigerian art. Findings reveal that the current discourse unwittingly frames Twentieth Century Nigerian art as a time-lag reactionary mimesis of Euro-American modernism. This research contends that such narrative blocks strong evidences of avant-garde tendencies identified in the works of Aina Onabolu, Ben Enwonwu, Uche Okeke and others, which exhibited intellectual use of the subversive powers of art for institutional/societal interrogation. Drawing upon modernist theories as a compass for analyzing the works of the aforementioned, this paper concludes that rather than being a mundane product of contemporaneity, Twentieth Century Nigerian art was inspired by decolonization politics and constituted a culture-specific avant-gardism in which art was used to enforce change. Thus, a new modern art discourse is proposed that will reconstruct Twentieth Century Nigerian art as an expression of modernism parallel to Euro-American modernism.